Development of a Knockout Competition in Basketball: A Study of the Spanish Copa del Rey - Ibáñez, Sergio José; García-Rubio, Javier; Rodríguez-Serrano, David; Feu, Sebastián (Frontiers in Psychology, 2019)
Performance in basketball has been widely studied with regard to the results of the game, using the competition statistics. Few studies have analysed the play process from a dynamic viewpoint regarding tactical actions and styles of play. The general objective of this research was to analyse the development in the styles of play of play of the teams participating in the Spanish Copa del Rey, by studying the development of ball possessions (from start to finish) and the styles of play (attack and defence phases). The specific aim was to identify the relations between how possessions end and the style of play, as well as the relation between the duration of possession and the action of shooting and efficacy of the possession. All the matches corresponding to the Spanish Copa del Rey in Basketball in the seasons 2015/16, 2016/17 and 2017/18 were analysed, comprising a total of 3,865 possessions. To this end, two groups of variables were characterised which made it possible to define play, the development of possession (start and finish) and the style of play (attack and defence phase). An exploratory and descriptive analysis of the situational variables, development of possession and style of play was carried out to characterise the competition. The Chi-squared test and Cramer’s V coefficient were used to estimate the association among the categorical variables, interpreting the association among the categories using contingency tables. The results show a greater number of attacks in the final stages of the matches, with short possessions that end in baskets or rebounds, and positional attacks and individual half-court defences predominating. There were more shots in positional attacks and more fouls in transitions. It also was apparent that the competition is developing from one year to another. The Spanish Copa del Rey competition changes from season to season, revealing slight modifications in the teams’ styles of play, although there is stability in the fundamental play parameters, like the predominance of man-to-man defence, the duration of the attacks and the use of screens. The style of play conditions the finalisation of the possession.